Contemporary Islamic Education: Effective Strategies in Responding to Social and Cultural Challenges - Hafizul Husni; Firianto Firianto; Kasinyo Harto; Mardiah Astuti (Academia Open, 2025)
The general background of this study highlights the rapid transformation of contemporary Islamic education amid globalization, digitalization, pluralism, and secular value shifts that challenge traditional pedagogical models. The specific background shows that Islamic educational institutions are under increasing pressure to integrate technological innovation, multicultural competence, and moral formation to remain relevant. The knowledge gap lies in the limited scholarly synthesis that holistically maps effective strategies for balancing Islamic principles with the demands of modern social and cultural contexts. This study aims to identify adaptive, comprehensive strategies that strengthen the integrative role of Islamic education through curriculum reform, ICT integration, educator empowerment, and family–community collaboration. The results reveal that transformative, value-based, and technologically enriched approaches significantly enhance Islamic education’s responsiveness to global challenges. The novelty of this study lies in offering an integrated framework that connects ethical-spiritual formation with modern pedagogical innovation, grounded in literature from 2018–2025. The implications suggest that Islamic education can serve as a sustainable moral compass and social catalyst when it harmonizes faith, knowledge, and culture to develop intellectually competent, socially aware, and spiritually resilient learners. Highlights: Contemporary Islamic education must balance tradition with global social–cultural change. Integrative strategies—curriculum reform, ICT, and educator empowerment—enhance relevance. Harmonizing faith, knowledge, and culture strengthens learners’ moral and intellectual resilience. Keywords: Islamic Education, Globalization, Digitalization, Moral Development, Integrative Strategy